2015
DOI: 10.1002/chem.201502346
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Proton NMR in Hydrogen Bonds in Terms of Lone‐Pair and Bond Orbital Contributions

Abstract: NMR spectroscopic parameters of the proton involved in hydrogen bonding are studied theoretically. The set of molecules includes systems with internal resonance-assisted hydrogen bonds, internal hydrogen bonds but no resonance stabilization, the acetic acid dimer (AAD), a DNA base pair, and the hydrogen succinate anion (HSA). Ethanol and guanine represent reference molecules without hydrogen bonding. The calculations are based on zero-point vibrationally averaged molecular structures in order to include anharm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 85 publications
0
25
0
Order By: Relevance
“…Autschbach and co-workers have previously applied DFT to calculate 1 J OH in a variety of hydrogen bonded carboxylic acids. 64 They predicted that 1 J OH ranged from 42 Hz to 99 Hz and showed that 1 J OH was correlated to Wiberg bond indices (WBI) which quantify the bond order. 64 Scalar couplings can be measured with a J-resolved 46,[65][66] block at the beginning of the D-RINEPT sequence ( Figure 3C).…”
Section: Resultsmentioning
confidence: 99%
“…Autschbach and co-workers have previously applied DFT to calculate 1 J OH in a variety of hydrogen bonded carboxylic acids. 64 They predicted that 1 J OH ranged from 42 Hz to 99 Hz and showed that 1 J OH was correlated to Wiberg bond indices (WBI) which quantify the bond order. 64 Scalar couplings can be measured with a J-resolved 46,[65][66] block at the beginning of the D-RINEPT sequence ( Figure 3C).…”
Section: Resultsmentioning
confidence: 99%
“…29 Other theoretical studies showed that 1 H shielding is determined by σ-type orbital contribution, although in the case of the H-bonded proton, it was shown that 1 H-shielding contributions due to bonds and lone pairs of the acceptor atom are negligible. 26,3032 Furthermore, hydrogen bonds have a partial covalent character: The unoccupied σ* N–H orbital accepts electronic density from the lone pair of the opposite nitrogen or oxygen atom, which would actually lead to an accumulation of electronic density on the hydrogen atom. 33 In this work, we aim to clarify the electronic contributions in hydrogen bonds that give rise to the observed trend in 1 H-shielding values.…”
mentioning
confidence: 99%
“…[32][33][34][35][36][37][38][39] Owing to RAHB systems in many organic and coordination compounds, the hydrogen bond is conjugated with a p-electronic system,a nd the 1 HNMR resonance of the involved proton( > 12 ppm) is shifteds trongly downfield relative to that for ar egular hydrogen bond. Nevertheless, in originals ources, these roles of RAHB have often been disregarded,a nd some authors have even criticizedt he concept of RAHB in af ew cases.…”
Section: Discussionmentioning
confidence: 99%
“…When doubleb onds are not bridged only by as ingle bond (e.g.,i n6 -, 7-, or 8-membered H-bonded rings), thush ampering the conjugation,t hey are not involved in RAHB systems, [31][32][33][34][35][36][37][38][39] and are out of the scope of this Review.E xamples include dimers of aldehydes, of carboxylic acids and of pyridin-2-ol, as well as fulvenes (Scheme 2a-d), [31][32][33][34][35][36][37] and contrast, for example, with the case of b-diketones [24,[40][41][42] and( Z)-6-hydroxy-5-[(1methyl-2-oxoindolin-3-ylidene)methyl]pyrimidine-2,4(1 H,3H)dione [43] (Scheme 2e), in which resonance stabilization has ac onsiderable effect. [31][32][33][34][35][36][37][38][39] As mentioned above,i nR AHB, the hydrogen-bond donor and acceptora toms are connected through p-conjugated double bonds.…”
Section: Introductionmentioning
confidence: 99%